(untitled) - Johnson, Keith (Malden, M.A., 2012)
Fully revised and expanded, the third edition of Acoustic and Auditory Phonetics maintains a balance of accessibility and scholarly rigor to provide students with a complete introduction to the physics of speech. Newly updated to reflect the latest advances in the field. Features a balanced and student-friendly approach to speech, with engaging side-bars on related topics. Includes suggested readings and exercises designed to review and expand upon the material in each chapter, complete with selected answers. Presents a new chapter on speech perception that addresses theoretical issues as well as practical concerns.
Keywords: Ngữ âm, âm vị,Phonetics, acoustic